Total Knee Arthroplasty in the Valgus Knee - Mannino, Angelo; Weinberg, Maxwell E.; Scuderi, Giles R. (The Journal of Knee Surgery, 2023)
An estimated 10 to 15% of total knee arthroplasties (TKAs) are implanted for a diagnosis of arthritis when a valgus deformity is present. There are various techniques and considerations that must be considered for a successful TKA in a patient with a valgus deformity. This article provides a detailed summary of the anatomy, pathology, bone preparation, soft tissue management, implant selection, and complications when performing a TKA in a patient with valgus deformity.
Keywords: knee; arthroplasty; valgus